Quantification of Dermal Microcirculatory Changes after Topical Administration of Capsaicin: A Randomized Placebo-Controlled Study in 46 Subjects. Issue 9 (15th August 2022) - Schäfer, Ruth Christine; Sohn, Anna; Kersten, Anabel; Amr, Amro; Held, Manuel; Wenger, Andrea
Abstract: Background: Dermal blood flow is crucial for wound healing and survival of flaps in dermatologic surgery. To improve flap viability in cases of compromised perfusion topical agents can easily be applied. The aim of this placebo-controlled study was to characterize changes of DBF in healthy subjects by quantitatively assessing perfusion dynamics after application of capsaicin to establish a reference for measurements at injured sites. Methods: In 46 healthy subjects perfusion dynamics after local application with capsaicin and placebo was noninvasively assessed, determining cutaneous oxygen saturation, relative hemoglobin count and blood flow using an Oxygen-to-See device. Results: A significant raise in superficial (162% p  = 0.000) and deep (144%, p  = 0.000) skin oxygenation after 30 min was provoked. A highly significant raise in measurements of flow and velocity was present in superficial (523%, p  = 0.000) and deep (242%, p  = 0.000) sites. Conclusion: With the introduced model applied to observe changes in parameters of dermal blood flow in healthy subjects the authors can reliably monitor effects of topically administered capsaicin. This baseline can be used as reference for further studies in the settings of endangered flap survival or critically perfused wounds as has been proven in animal studies.